2018
DOI: 10.1590/s0102-699220183302014
|View full text |Cite
|
Sign up to set email alerts
|

O suicídio no Brasil contemporâneo

Abstract: Resumo Como um grave problema de saúde pública, não é recente o interesse das organizações internacionais pela problemática da mortalidade por suicídio, tanto nos distintos grupos etários como nos segmentos socioeconômicos. A sociologia, desde suas origens, oferece explicações a respeito dos determinantes estruturais desse fenômeno. As estatísticas oficiais indicam que o Brasil é o oitavo país com o maior número de suicídios no mundo, todavia, existem poucos estudos que se dedicam a tratar do assunto, ainda qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
2
0
7
Order By: Relevance
“…It was observed that, from 5.576 Brazilian municipalities, 855 have a higher SMR value if compared to the whole country, once the municippalities with significative results are located, mainly, in the federative units of Mato Grosso and Rio Grande do Sul (Table 1). Such result confirms the data gathering conducted by Silva et al (2018), finding the highest rates of suicide per 100.000 inhabitants belonging to the states of Rio Grande do Sul, Santa Catarina and Mato Grosso do Sul.…”
Section: Total Suicide In Brazilsupporting
confidence: 89%
See 1 more Smart Citation
“…It was observed that, from 5.576 Brazilian municipalities, 855 have a higher SMR value if compared to the whole country, once the municippalities with significative results are located, mainly, in the federative units of Mato Grosso and Rio Grande do Sul (Table 1). Such result confirms the data gathering conducted by Silva et al (2018), finding the highest rates of suicide per 100.000 inhabitants belonging to the states of Rio Grande do Sul, Santa Catarina and Mato Grosso do Sul.…”
Section: Total Suicide In Brazilsupporting
confidence: 89%
“…Among the federative units with a higher "strengh to die of suicide, in the population, as a whole, were found 13 with significative results of SMR (Table 1), being some of them considered "neighbors". This result was also presented by Silva et al (2018) once he has shown an existing spatial autocorrelation related to the practice of suicide, classifying the municipalities of the South and Center-West regions as the ones with high rates of suicide. Among the main causes of mortality by suicide, it's possible to mention the job, the unemployment and the social isolation as being crucial.…”
Section: Total Suicide In Brazilsupporting
confidence: 54%
“…No Brasil as LAI passaram por um crescimento de 62,5% entre os períodos de 1980 a 2000, apresentando taxas maiores que acidentes de trânsito e homicídios. Em 2018, o país registrou 12.104 óbitos por LAI, e acrescenta-se a isso que muitas mortes não são registradas como suicídio, sem contar com as TS que acontecem em uma esfera 10 vezes superior aos casos consumados (Silva, Prates, Cardoso, & Castro, 2018).…”
Section: Introductionunclassified
“…According to the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística, IBGE) data, the prevalence of notifications per 1,000 in a population of 108,728 inhabitants, taking into account the number of people in each age group as in our data was5.8 cases/1,000 inhabitants 15 -19 years old, with a population of 8,466 people; 2.6 cases/1,000 inhabitants 20 -39 years old, with a population of 36,880 people; and 4.1/1,000 inhabitants 40 -59 years old, with a population of 28,656 people (IBGE, 2010) (Figure 2). These data show that the highest incidence of cases occurred in the 15 -19 years old group, even though the total number of notifications was higher in the 20 -39 years old group; this may be associated with what happened in Brazil between 1980 and 2010, a period in which the highest suicide rates were related to factors of low social integration as described by Silva et al (2018). Birigui-SP, having an industrial city profile (SEADE, 2020), may reflect the behavior of low social integration especially in youngsters, who were affected by a limited opportunity to enter the labor market.…”
Section: Resultsmentioning
confidence: 67%